RESEARCH ON SEMI-ACTIVE CONTROL METHODS FOR STADDLE MONORAIL′S PANTOGRAPH WITH SLIDING MODE VARIABLE STRUCTURE (MT) - CHEN Lin; XIONG Jun; WANG ShangQing (Jixie qiangdu)
Staddle monorail use rigid catenary, which often produce strong rigid vibrations and violent fluctuations in contact forces affecting pantograph receiving quality and service life during operation. Therefore, a semi-active control method for staddle monorail′s pantograph with sliding mode variable structure is proposed. The pantograph model with two lumped masses and magneto rheological damping are selected as the research object and the operating mechanism respectively. Firstly, the coupling relationship of the staddle monorail′s pantograph-catenary system is studied and the dynamics equations are derived. Secondly, with the support of the above theory, the active control system for pantograph is built by Simulink simulation method combined with sliding mode variable structure control. Finally, the reverse model of magneto rheological damper is established to realize semi-active control for pantograph. When magneto rheological damper receives the control signal transmitted by the controller, it outputs the desired control force by adjusting the current and finally acts on the pantograph, effectively solving the problem of violent fluctuation of contact force. The experimental results show that the proposed method is more accurate to control the contact force of the pantograph-catenary system, significantly reduces the standard deviation of the contact force by more than 17.34%, and avoids the occurrence of the offline situation of the pantograph-catenary system. The stability and superiority of the proposed method in improving the current quality of the pantograph-catenary system and prolongating the service life of the pantograph are verified.